Efficacy of the Suboccipital Paracondylar-Lateral Cervical Approach: The Series of 64 Jugular Foramen Tumors Along With Follow-Up Data - Wang, Xiangyu; Yuan, Jian; Liu, Dingyang; Xie, Yuanyang; Wu, Ming; Xiao, Qun; Qin, Chaoying; Su, Jun; Zeng, Yu; Liu, Qing (Frontiers in Oncology, 2021)
Objective: Complete resection of jugular foramen tumors with minimal cranial nerve complications remains challenging even for skilled neurosurgeons. Here, we introduce a modified paracondylar approach, named the suboccipital paracondylar-lateral cervical (SPCLC) approach for this purpose. We also share the follow-up data of our series and discuss the advantages and limitations of this modified paracondylar approach. Methods: We included 64 patients with jugular foramen tumors who underwent surgery by the same senior neurosurgeon between November 2011 and August 2020. All patients were treated with the SPCLC approach, which aimed for gross total tumor removal in a single-stage operation. The clinical characteristics, including preoperative and postoperative neurological status, the extent of surgical resection, and follow-up data were retrospectively acquired and evaluated. Results: There were 48 schwannomas, nine meningiomas, three paragangliomas, one hemangiopericytoma, one chordoma, one endolymphatic sac tumor, and one Langerhans’ cell histiocytosis. The median age of our patients was 43 years (range: 21–77 years). Dysphagia, hoarseness, and tongue deviation were observed in 36, 26, and 28 patients, respectively. Thirty-two patients had hearing function impairments, including hearing loss or tinnitus. Gross total resection was achieved in 59 patients (59/64, 92.2%). Gamma Knife treatment was used to manage residual tumors in five patients. Postoperatively, new-onset or aggravative dysphagia and hoarseness occurred in 26 and 18 cases, respectively. Nine patients developed new-onset facial palsy, and one patient developed new-onset hearing loss. There were no cases of intracranial hematoma, re-operation, tracheostomy, or death. At the latest follow-up, hearing loss and tinnitus had improved in 20 cases (20/32, 62.5%), dysphagia alleviated in 20 cases (20/36, 55.6%), and hoarseness improved in 14 cases (14/26, 53.8%). Over a mean follow-up period of 27.8±19.5 months (range: 3–68 months), tumor recurrence was observed in one patient. Conclusion: The SPCLC approach, modified from the paracondylar approach, and was less invasive, safe, and efficient for certain jugular foramen tumors. Taking advantage of the anatomic understanding, clear operational vision, and appropriate surgical skills, it is possible to achieve gross total tumor removal and the preservation of neurological function.